Vitamin D, Depressive Symptoms, and Covid-19 Pandemic - Ceolin, Gilciane; Mano, Giulia Pipolo Rodrigues; Hames, Natália Schmitt; Antunes, Luciana da Conceição; Brietzke, Elisa; Rieger, Débora Kurrle; Moreira, Júlia Dubois (Frontiers in Neuroscience, 2021)
Since the COVID-19 outbreak, studies across diverse countries have strongly pointed towards the emergence of a mental health crisis, with a dramatic increase in the prevalence of depressive psychopathology and suicidal tendencies. Nutritional factors such as vitamin D have been associated with an increased risk of mental health problems as well as individual responses to stress. Studies have discussed the relationship between low serum vitamin D concentrations and depression, suggesting that maintaining adequate concentrations of serum vitamin D seems to have a protective effect against depression. The optimal vitamin D status was found to contribute to improved serotonergic neurotransmission deficits in an experimental depression model by regulating serotonin synthesis. The signaling of 1,25-dihydroxyvitamin D3, the active form of vitamin D, through VDR induces the expression of the gene TPH2, influences the expression of serotonin reuptake transporter (SERT) as well as the levels of monoamine oxidase-A (MAO-A), the enzyme responsible for serotonin catabolism. Vitamin D also presents a relevant link with chronobiological interplay. Evidence suggests a mediatory role of vitamin D in the sleep-wake cycle since the lower concentrations of vitamin D were correlated with impaired sleep quality and abbreviated sleep duration, point to its influence on melatonin metabolism, which is synthesized from the metabolism of serotonin. In this Perspective, we discussed the significant role of vitamin D in the elevation of stress-related depression symptoms during the COVID-19 pandemic.